A Confluence of Transatlantic Networks : Elites, Capitalism, and Confederate Migration to Brazil - Jarnagin, Laura (Book collections on Project MUSE., 2008)
A Confluence of Transatlantic Network demonstrates how portions of interconnected trust-based kinship, business, and ideational transatlantic networks evolved over roughly a century and a half and eventually converged to engender, promote, and facilitate the migration of southern elites to Brazil in the post-Civil War era. Placing that migration in the context of the Atlantic world sharpens our understanding of the transborder dynamic of such mainstream nineteenth-century historical currents as international commerce, liberalism, Protestantism, and Freemasonry. The manifestation of these transatlantic forces as found in Brazil at midcentury provided disaffected Confederates with a propitious environment in which to try to re-create a cherished lifestyle.